Evaluating Excuses: How the Public Judges Noncompliance (Journal of Behavioral Public Administration, 2023)
The political actors who make policy often delegate their implementation to others. Yet for a variety of reasons, ranging from intransigence to incompetence, political agents tasked with implementation may not faithfully implement policies. If those charged with implementation can frame their noncompliance in a way that engenders sympathy, implementors may be able to disrupt the policymaking process with limited public backlash. We examine if the public's willingness to excuse noncompliance varies with the implementing actor's rationale for its failing to carry out the policy. Drawing on a survey experiment fielded in Germany, we find that the public is more sympathetic to resource-based, rather than principled, justifications for noncompliance, though the size of the effect is small. Further, contrary to fears that the pandemic would decay democratic functioning by leading citizens to be more forgiving of emergency-based inaction, we find no evidence that the public is more accepting of noncompliance justified on the base of the pandemic.